The collected poems of Robert Louis Stevenson - Stevenson, Robert Louis, 1850-1894 (Edinburgh University Press, 2003)
A new edition of RLS's poetry, including many previously unpublished pieces.
Keywords: Stevenson, Robert Louis, -- 1850-1894.; Stevenson, Robert Louis, -- 1850-1894; Stevenson, Robert Louis.; Great Britain -- Religion -- 17th century.; Grande-Bretagne -- Religion -- 17e siècle.; LITERARY CRITICISM -- General.; Religion; Great Britain; Lyrik; Kommentar; 18.05 English literature.; 1600-1699; poetry.; Poetry; Poems (texts); Poetry.; Poésie.